Reconstructing the braided hair styles of the slab burial culture from stelae stone and petroglyph (Studia Archaeologica, 2025)
The main source for identifying how the people of the Slab burial culture make and style their hair is the monuments of the burial and petroglyph which were left by them. In additionally, it is how the ancient nomads of the Bronze and Early Iron age who lived in the territory of Mongolia they make and style their hair the question one of the exciting research topic. Therefore, now we are trying to identify this question only within the context of the Slab burial culture. To find out the answer the question, we analyzed and categorized depiction of people on the enclosure of slab burials, the image of braids on the back side of statue stones erected in the certain distance to the east of the burial, and human figures in petroglyph. Through this comparative method, we determined the meaning, function, and gender of those representations as follows. According to the research results, it is common to find the images of people performing dance-like movements carved on the enclosure stones of slab burials, in many case on slabs at the head or foot of the burials. These ritual scenes are mainly led by men. As viewing by their hairstyles, the men are depicted with a single braid, women are shown with two braids. On the stelae stones, the depiction of a single braid may indicate that the statue was erected in honor of a male individual, possibly the burial’s owner.Дөрвөлжин булшны соёлынхны гэзэг үсний заслыг хөшөө чулуу болон хадны зургаас тодруулах нь Хураангуй: Дөрвөлжин булшны соёлын хүмүүс гэзэг үсээ хэрхэн засаж янзалдаг байсныг тодруулах гол эх сурвалж бол тэдний үлдээсэн булш оршуулга болон хадны зургийн дурсгал юм. Монгол нутагт оршин амьдарч байсан хүрэл, төмрийн түрүү үеийн эртний нүүдэлчид гэзэг үсээ ямар хэлбэрээр засаж гоёдог байсан тухай асуудал судалгааны нэгэн сонирхолтой сэдэв болохын хувьд бид энэ удаад зөвхөн дөрвөлжин булшны соёлын хүрээнд уг асуудлыг тодруулахыг хичээв. Энэ асуултад хариулт олох үүднээс дөрвөлжин булшны хашлага чулуун дээрх хүмүүсийн дүрслэл, булшнаас зүүн тийш тодорхой зайд босгосон хөшөө чулууны ар тал дахь гэзэгний дүрслэл болон хадны зургийн хүний дүрүүдийг хооронд нь харьцуулан ангилах аргаар судалгааны хэрэглэгдэхүүнээ бүрдүүлж тэдний утга агуулга, үүрэг зориулалт, нас хүйсийг дараах байдлаар тодорхойлов. Судалгааны үр дүнгээс харахад дөрвөлжин булшны хашлага чулуун дээрх бүжиг мэт хөдөлгөөн хийж буй хүмүүсийг ихэвчлэн булшны хөл эсвэл толгой талын хавтан чулуун дээр дүрслэх нь түгээмэл ба уг ёслолыг голчлон эрчүүд магнайлан гүйцэтгэж байна. Эдгээр хүмүүсийн үс гэзгээ зассан байдлаас харахад эрчүүд үсээ нэгээр, эмэгтэйчүүд хоёр салаа болгон гөрснөөр дүрсэлжээ. Харин хөшөө чулуун дээр нэг салаа гэзгийг дүрслэн харуулж буй нь тухайн булшны эзэн болох эрэгтэй хүнд зориулан босгосон байж болох юм.Түлхүүр үг: Дөрвөлжин булш, гэзэг үсний засал, хөшөө чулуу, хадны зураг